Report
1941-11 038-0024-014 Published by National Joint Committee for Spanish Relief, 39, Victoria Street, Westminster, S.W.1 and printed in Great Britain by Knapp, Drewett & Sons Ltd., Printers, Westminster, S.W.1—25390v 292/946/38/24(XIV)